(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Transboundary rivers pose significant challenges in their utilization due to complex geopolitical, environmental, and socio-economic factors. This article examines the problems associated with harnessing these rivers for various purposes and discusses the implications of such challenges. Through an analysis of data on transboundary rivers, key issues such as water scarcity, conflicts over allocation, and environmental degradation are highlighted. Understanding these challenges is crucial for developing effective management strategies and fostering cooperation among riparian states. This article provides a comprehensive analysis of the challenges associated with the utilization of transboundary rivers, focusing particularly on Central Asia. It explores key issues such as water scarcity, geopolitical conflicts, environmental degradation, and the lack of cooperation among riparian states. Through a methodical approach that includes literature review, data analysis, and consideration of scientific research, the article examines the multifaceted nature of transboundary river management.